Explaining the d-q Magnetic Couplings Theoretically in Saturated Smooth Air-Gap AC Machines - Khlifi, M. A. (Engineering, Technology & Applied Science Research, 2019)
The current paper discusses the theoretically detailed physical analysis of the effects of main flux saturation in smooth air gap AC machines. For that purpose, three sections are presented. The first one deals for presenting equivalence saturation-air gap. The second presents the equivalence of inductances between saturation induction machines and a dismounted salient pole synchronous machine. The method analyzes the leakage inductances that properly represent the corresponding leakage fluxes. The third section treats the physical interpretation of the cross-saturation. It is possible to show that the equations and physical picture in a saturated smooth-air-gap machine are similar to the equations and physical picture in a non-saturated salient-pole machine, where mutual coupling exists between the direct and quadrature axes and the self-inductances are also different on the non-salient part of the machine due to the variation of the reluctance with the rotor angle.